Diagnostic and prognostic value of lipopolysaccharide binding protein and soluble urokinase plasminogen activator receptor in dogs with parvoviral enteritis - Alparslan Burak Gucsav; Enes Akyuz (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to evaluate the diagnostic and prognostic values of lipopolysaccharide binding protein (LBP) and soluble urokinase plasminogen activator receptor (suPAR) in dogs with parvoviral enteritis (CPV). Materials and Methods: Twenty dogs, 1-6 months old, from different breeds and genders were enrolled in the study. The presence of parvoviral enteritis confirmed by rapid test kit and ongoing bloody diarrhea. Ten healthy age matched dogs were enrolled in the study as control group. Blood samples were taken once from all of the dogs from Vena cephalica antebrachi. A complete blood cell count was measured from taken sample. Serum biochemical analyses were performed from the serum samples Results: Total leukocyte count, erythrocyte count, hemoglobin count and hematocrit percentage were significantly lower in the dogs with CPV compared to the control group (p<0.05). While creatinine (p=0.040), urea (p=0.036), total bilirubin (p=0.011), ceruloplasmin (p=0.008), haptoglobin (p<0.001) and LBP (p=0.011) concentrations were significantly higher in the dogs with CPV compared to the control group, albumin (p=0.005) and suPAR (p=0.012) concentrations were found to be low. Conclusion: Ceruloplasmin, haptoglobin, LBP and suPAR were found to be diagnostically and prognostically important in dogs with parvoviral enteritis.